A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Recent advances in therapeutic agents for uranium poisoning: a comprehensive review - Juan Li; Wenrun Li; Feng Huang; Qiuchi Wang; Hongjia Liu; Liyi Chen; Qiuping Wang; Yong Li; Shiyan Fu; Yazhen Zhao; Yonghong Ran; Yuhui Hao (BioMetals, 2026)

Microwave-assisted synthesis of FeN Co-doped ZIF-8 derived carbon for low-concentration lithium recovery via CDI: Adsorption performance and mechanism - Yongsi Xie; Jiemei Fu; Chunxue Li; Juan Luo; Rui Ma; Shichang Sun (Desalination, 2026)

A flexible piezoresistive pressure sensor with an interlocking microstructure based on modulated corona electric field - Chenghang Yu; Jian Xu; Fu Lv; Bing Liu; Juan Li; Xin Li; Zijian Hong; Yongjun Wu; Yuhui Huang (Chemical Engineering Journal, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Broad synergistic effects of an AMP with multiple antibiotics against drug-resistant bacteria via multifaceted mechanisms - Zifan Ye; Xia Wang; Zhouye Xu; Taizhong Wang; Juan Wang; Shuangyu Li; Xiangjin Kong; Jingjing Zhang; Xudong Jiao; Lei Fu; Yipeng Wang (Science China Life Sciences, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Imbalance of the AKT/MAPK signaling axis mediates the exacerbation of Alzheimer's disease pathology by simulated particulate air pollution from Shihezi in APP/PS1 mice - Xuening Li; Linglong Meng; Qiang Niu; Runjiang Ma; Yuhan Li; Hailing Zhou; Xiaoya Fu; Wenjie Chen; Juan Tang; Shangzhi Xu (NeuroToxicology, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Multifaceted regulation of immune cells in radiation-induced pulmonary fibrosis: from mechanistic insights to targeted therapies - Li Shen; Wanrong Zhang; Yonghao Yang; Zhiqiang Du; Shiyan Fu; Feng Huang; Xiaoyu Yang; Juan Li; Yonghong Ran; Yuhui Hao (Inflammation Research, 2026)

Genome-wide identification and functional characterization of the CaD27 gene family in pepper under cold stress - Jian Li; Jie Li; Hongbo Fu; Yanzhuang Wang; Juan Li; Minkun Pei; Jihua Yu; Ping Yang (Plant Molecular Biology, 2026)

Impact of soil compaction and seasonal freeze-thaw cycles on the microstructural evolution and aggregate stability of Mollisol - Boxiang Zhang; Bo Liu; Shuang Li; Juan Fu; Yanfeng Jia; Haoming Fan; Chengjiu Guo; Fangli Su; Renming Ma (Soil and Tillage Research, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

An enhanced cow-teat-detection model for automatic teat-cup-attachment devices - Mengjie Li; Juan Wang; Na Li; Yaju Liu; Xue Cheng; Xinpei Fu; Sirui Li (Biosystems Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Depleted uranium exposure induced ferroptosis in renal cells via the ETHE1/P38-MAPK pathway - Feng Huang; Wenrun Li; Juan Li; Yonghong Ran; Shiyan Fu; Li Shen; Qi Li; Xiaoyu Yang; Yazhen Zhao; Yuhui Hao (Archives of Toxicology, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

APOE Lipoprotein Particles: Pathophysiology, Therapy, and the Crosstalk in Alzheimer’s Disease and Cardiovascular Disease - Chan Liu; Juan Liu; Yan-Yang Wang; Shang-Fu Xu; Li-Mei Yu (Molecular Neurobiology, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Integrating lewis acid/base pairs and hydroxyfunctional groups as dual adsorption sites into porous biochar fiber for enhanced iodine capture - Hongquan Fu; Xiao Wang; Liping Li; Zhenyang Li; Jinming Chang; Fang Liao; Hejun Gao; Juan Zhang; Yunwen Liao (Journal of Water Process Engineering, 2025)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Late Cenozoic Climates and Mountains Drove Diversification of the Pardosa laura Species Complex From Eastern China - Li‐Juan Liu; Dan Fu; Shu‐Qiang Li; Yu‐Fa Luo (Journal of Biogeography, 2025)
Aim To test how evolutionary processes of spiders in mountain ranges of eastern China were in response to environmental changes, we analyze the correlation between diversification of the Pardosa laura species complex (Araneae, Lycosidae) and historical climates and mountains in this region. Methods We reconstruct phylogenetic relationships and patterns of phylogeography and genetic diversity using mtDNA data from samples spanning the full range of the species complex P. laura in eastern China. Results The P. laura species complex clustered into four lineages: Lineage I includes five haplotypes from the areas to the north of the Yinshan‐Yanshan Mountains; Lineage II consists of 23 haplotypes from the areas between the Qinling Mountains–Huaihe River Line and the Nanling Mountains; Lineage III and IV are composed of 21 and 62 haplotypes, respectively, from the areas between the Yinshan‐Yanshan Mountains and the Nanling Mountains. Each lineage corresponds to that, grouped from haplotype network analyses, with the same geographic distribution areas. All four lineages initially diversified during about 1.43 and 0.24 Ma ago (Ma) in relation to the Pleistocene glacial‐inglacial cycles. The biogeographic reconstructions suggest that the species complex P. laura most likely originated in central China around 7.68 (11.17–4.85) Ma in relation to the recent ( approximately 8 Ma) expansion of grasslands and retraction of forests. The inter‐colony dispersal between central China and northeastern China occurred during the late Neogene, between around 7.68 and 3.14 Ma. Central China is an important dispersal center, with dispersal to southwestern and northern China between the late Pliocene and middle Pleistocene, approximately 3.14–2.89 and 2.89–1.43 Ma, respectively. Main Conclusions The contemporary genetic structure of the P. laura species complex presents a high correlation between lineages and geographic distribution. The historical phylogeographic patterns suggested that the late Cenozoic climate changes and the mountainous corridors and isolation events, as well as the lineage dispersals and ecological adaptations shaped the diversification of a spider species complex in eastern China over long timescales.

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Formation of reactive oxidants from Fe(II)-bearing minerals in oxic environments: A review - Jieyun Lin; Juan Zhou; Yu Fu; Jiamin Cai; Shi Chen; Tao Wang; Jiang Li; Shaoqi Zhou; Yuanyuan Liu (Journal of Hazardous Materials, 2025)

Exogenous DBT and overexpression of deoR improved the waste tire rubber desulfurization ability of a newly isolated Escherichia sp. strain - Yao Lu; Fang-Qi Gao; Yu-Yan Wang; Ying-Wen Fu; Zhuo-Miao Li; Juan Xie; Gao-Qiang Liu; Yong-Nan Liu (Journal of Hazardous Materials, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Boosting proton-coupled electron transfer in H2O2 photosynthesis with sulfonic acid-functionalized carbon nitride - Yayao Li; Zhi Li; Qinlin Yuan; Juan Zhang; Yunzhi Fu; Mingshan Zhu (Chemical Engineering Journal, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

Probing the fitness landscape of the influential nodes for the influence maximization problem in social networks - Jianxin Tang; Jiaqiang Fu; Xinyue Li; Lele Geng; Juan Pang (Swarm and Evolutionary Computation, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

China’s marine plastic pollution governance path: focusing on the judicial positioning of PIL initiated by procuratorial agencies - Ben-Chao Fu; Chuan-Kai Guo; Xiu-Juan Li; Hai-Dong Cai; Jin-Hua Guo; He-Ran Li (Frontiers in Marine Science, 2025)
Can procuratorial agencies play a key role in China’s governance of marine plastic pollution (MPPG)? Within the current discussions about the legal framework of China’s MPPG, courts, marine environmental regulatory authorities, procuratorial agencies, and environmental protection organizations are typically seen as the main stakeholders. However, the role of procuratorial agencies, as the statutory entity for initiating PIL in marine environmental protection, has been significantly overlooked. This raises a range of questions including how should procuratorial agencies leverage their advantages in PIL to enhance the diversity of participants in the litigation process? What inherent challenges exist in marine environmental lawsuits? What substantive and procedural obstacles will procuratorial agencies face when engaging in MPPG-related litigation? This study argues that procuratorial agencies, by fulfilling their public interest litigation (PIL) function in marine environmental protection, can effectively improve MPPG governance. The study focuses on issues such as the unclear prerequisites for initiating MPPG-related lawsuits by procuratorial agencies, the criteria for selecting diverse litigation models, and the applicability of procuratorial agencies’ PIL in foreign-related cases.

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

New thiohydantoin derivatives from the roots of Lepidium meyenii - Wen-Xin Liu; Jun Li; Cheng-Juan Liao; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2025)

Enhanced selective removal of lead from battery industry wastewater using MoS2@PbCO3 composite seeds via a nucleation crystallization pelleting process - Yadong Wang; Yabo Shang; Zhihao Fu; Keqian Li; Juan Shi; Lu Xu; Pengkang Jin; Xin Jin; Xiaochang C. Wang (Journal of Hazardous Materials, 2025)

Efficient separation of layered oxide cathode materials and Al collectors in spent lithium-ion batteries - Zhiyue Fu; Weihao Zeng; Juan Wang; Yu Li; Shichun Mu (Journal of Cleaner Production, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Effect of thermostatic freezing on physicochemical indexes and metabolism of shrimp (Solenocera melantho) - Yongfa Cheng; Xinling Liu; Juan Shi; Shiqian Fu; Huicheng Yang; Liqing Wu; Yongjiang Lou; Yongyong Li (Food Bioscience, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

Mesenchymal stem cell exosomes regulate TGFβ/Smad3 by decreasing the METTL3-NEAT1 axis to inhibit scar progression after breast surgery - Juan Du; Jincheng Wu; Qinqin Song; Shuangru Li; Youwang Hong; Aizaz Anwar; Quanyou Fu; Jisong Liu (Journal of Molecular Histology, 2025)

Ozone-mediated carboxylation: a strategy for enhanced organic matter removal via in-situ crystallization of hardness ion - Keqian Li; Yujia Han; Yi Chen; Zhihao Fu; Heng Quan; Yadong Wang; Yabo Shang; Juan Shi; Pengkang Jin; Xin Jin (Journal of Cleaner Production, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Construction of oxygenated porous biochar by dual activation method for highly efficient removal of tetracycline from aqueous solution - Jiaxin Hu; Bingyuan Huang; Baoyu Li; Hongquan Fu; Juan Zhang; Hejun Gao; Yunwen Liao (Journal of Water Process Engineering, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

Electroacupuncture Promotes the Generation of Intestinal Treg Cells After Ischemic Stroke by Foxp3 Acetylation Regulation - Yonglin Chen; Ling Ouyang; Xinyi Yang; Bufan Wu; Lingling Meng; Jialin Gu; Yaling Wang; Juan Li; Jingjing Zhang; Xinyue Jing; Shengfeng Lu; Lanying Liu; et al. (Molecular Neurobiology, 2025)

Effects of dietary hydroxy-cinnamic acid derivatives on growth, muscle, and intestinal parameters of Tilapia (Oreochromis niloticus) - Qing Li; Min Fu; Shengqin Zhu; Juan Liu; Yanqing Li; Zhiyong Xue; Zhigang Zhou; Lijuan Yu (Fish Physiology and Biochemistry, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Rapid analysis of salivary glucose content using MOF/MIPs biomimetic microfluidic paper chips - Ningning Li; Ying Zhou; Hao Sun; Nan Wang; Nan Yang; Peiyao Ren; Lanjun Fu; Yiming Zhang; Wei Liu; Yanjie Li; Juan Jin (Chemical Engineering Journal, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Synthesis of lipophilic vitamin C and evaluation of its antioxidant performance in sunflower seed oil frying - Min Fu; Juan Liu; Qing Li; Shengqin Zhu; Zhiyong Xue; Lijuan Yu; Zhigang Zhou (Food Chemistry, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Impact of greening trends on biogenic volatile organic compound emissions in China from 1985 to 2022: Contributions of afforestation projects - Yichao Gai; Lei Sun; Siyuan Fu; Chuanyong Zhu; Changtong Zhu; Renqiang Li; Zhenguo Liu; Baolin Wang; Chen Wang; Na Yang; Juan Li; Chongqing Xu; et al. (Science of The Total Environment, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Early detection of rubber tree powdery mildew using UAV-based hyperspectral imagery and deep learning - Tiwei Zeng; Yong Wang; Yuqi Yang; Qifu Liang; Jihua Fang; Yuan Li; Huiming Zhang; Wei Fu; Juan Wang; Xirui Zhang (Computers and Electronics in Agriculture, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Impact of nanoplastics on Alzheimer ’s disease: Enhanced amyloid-β peptide aggregation and augmented neurotoxicity - Xiaoli Gou; Yongchun Fu; Juan Li; Juan Xiang; Minghui Yang; Yi Zhang (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Screening, probiotic properties, and inhibition mechanism of a Lactobacillus antagonistic to Listeria monocytogenes - Xinyu Yang; Zheng Peng; Mengni He; Zhibin Li; Guihua Fu; Shaolei Li; Juan Zhang (Science of The Total Environment, 2024)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

The effect of multiple factors on water-soluble inorganic ions in diesel particulate matter emissions - Mengqi Fu; Taosheng Jin; Liang Qu; Shuangxi Liu; Kaibo Lu; Youzhen Tao; Shuai Zhao; Zhenguo Li; Penghui Li; Juan Liu (Journal of Hazardous Materials, 2023)

Triplet chromophoric dissolved organic matter regulating the phototransformation and toxicity of imidacloprid in paddy water - Yu Zeng; Qinglong Fu; Dionysios D. Dionysiou; Mingyang Zhang; Mabo Li; Bo Ye; Ning Chen; Juan Gao; Yujun Wang; Dongmei Zhou; Guodong Fang (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Seasonal–interannual–decadal variations of sea level in the South China Sea and connections with the tropical–subtropical Pacific - Juan Li; Wei Tan; Wenjin Sun; Lina Yang; Lei Lin; Qingjun Fu (International Journal of Climatology, 2023)
Different timescale contributions to the sea‐level variation in the South China Sea (SCS) are evaluated in this paper. On seasonal timescale, the large variance of the sea‐level anomaly (SLA) could account for more than 70% of the monthly sea‐level variation in the western shallow continental shelf and the area of Luzon cold eddy. Besides, the seasonal explained variance percentage (skill) has 2 weak centres (50%–70%) off eastern Vietnam, which is related to the summertime eddy pair in the SCS. On interannual‐to‐decadal (low‐frequency) timescale, the skill has two large‐value regions (Zone A and Zone B). Zone A is characterized by double centres off eastern Vietnam, but the meridional position of the double centres is farther north than that of the eddy pair. The skill in Zone A is in the range of 35%–55%, and about 50%–70% of the low‐frequency variation comes from the steric effect. Zone B is off the west coast of the Philippines. The skill in Zone B increases southward, and it is dominated by the wind‐induced dynamic process which is attributed to the remote Rossby wave from the tropical Pacific. Based on the S‐EOF analysis, the SEOF‐1 mode mainly portrays the decadal variation of the SLA, while the SEOF‐2 mode reflects the interannual variation of the SLA. In Zone B, almost all of the low‐frequency variation could be attributed to ENSO and PDO, especially to PDO which has a larger contribution. However, the double centres in Zone A are governed by the SCS summer monsoon, instead of ENSO and PDO.

Pd3Pb bimetallic aerogels for anti-poisoned oxygen reduction reaction - Hui Fu; Juan Wang; Yao Chen; Honggang Huang; Yang Wang; Hanjun Li; Feili Lai; Longsheng Zhang; Nan Zhang; Jiadong Chen; Tianxi Liu (Chemical Engineering Journal, 2023)

Research progress and applications of colorful Brassica crops - Fuyan Li; Yingying Gong; Annaliese S. Mason; Qian Liu; Juan Huang; Miao Ma; Meili Xiao; Huadong Wang; Donghui Fu (Planta, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Removal of iodide anions in water by silver nanoparticles supported on polystyrene anion exchanger - Li Li; Su-Juan Yu; Rong-Gang Zheng; Peng Li; Qing-Cun Li; Jing-Fu Liu (Journal of Environmental Sciences, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Fluid evolution and ore genesis of the A'gui Cu deposit in southern Great Xing'an Range, Northeast China: Evidence from fluid inclusion and C–H–O–S–Pb isotopes - Xue Wang; Ke-yong Wang; Li-juan Fu; Qing-ying Zhao; Qing-fei Sun; Chao Zhang (Geochemistry, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Effects of fabrication of conjugates between different polyphenols and bovine bone proteins on their structural and functional properties - Li Pan; Jingya Chen; Huihui Fu; Niannian Wang; Junrong Zhou; Shuyao Zhang; Shiling Lu; Juan Dong; Qingling Wang; Haiyan Yan (Food Bioscience, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Construction of the dynamic model of SCI rehabilitation using bidirectional stimulation and its application in rehabilitating with BCI - Zhengzhe Cui; Juan Lin; Xiangxiang Fu; Shiwei Zhang; Peng Li; Xixi Wu; Xue Wang; Weidong Chen; Shiqiang Zhu; Yongqiang Li (Cognitive Neurodynamics, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

A calculation model for radionuclide dispersion in the ocean and its credibility evaluation - Peng Xu; Tao Zhou; Zhongguang Fu; Juan Chen; Zichao Li (Annals of Nuclear Energy, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Performance of oxalate-doped hydroxyapatite as well as relative contribution of oxalate and phosphate for aqueous lead removal - Haojie Fu; Xinxin Li; Guoqing Dai; Maojuan Bai; Wei Sheng; Xu Zhang; Juan Liu; Lei Wang (Science of The Total Environment, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Spatial transcriptome analysis of long non-coding RNAs reveals tissue specificity and functional roles in cancer - Kang Xu; Xiyun Jin; Ya Luo; Haozhe Zou; Dezhong Lv; Liping Wang; Limei Fu; Yangyang Cai; Tingting Shao; Yongsheng Li; Juan Xu (Journal of Zhejiang University-SCIENCE B, 2023)

Extraction and spatiotemporal changes of open-pit mines during 1985–2020 using Google Earth Engine: A case study of Qingzhou City, Shandong Province, China - Liu Ruifeng; Yuan Kai; Li Xing; Liu Xiaoli; Zhao Xitao; Guo Xiaocheng; Fu Juan; Cao Shixin (Environmental Monitoring and Assessment, 2023)

Separation of Panax notoginseng saponins on modified rosin ester-bonded silica stationary phase and its mechanism - Wen-Bo Xie; Hao Li; Lei Zeng; Li-Juan Jiang; Wen Li; Lu Xia; Fu-Hou Lei (Analytica Chimica Acta, 2023)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Reconstruction of large complex sand-wave bathymetry with adaptive partitioning combining satellite imagery and sparse multi-beam data - Huaguo Zhang; Juan Wang; Dongling Li; Bin Fu; Xiulin Lou; Ziyin Wu (Journal of Oceanology and Limnology, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Transcriptome Analysis of Sophora davidii Leaves in Response to Low-Phosphorus Stress - Xin Zhao; Li-Juan Huang; Li-Li Zhao; Pu-Chang Wang; Xiao-Fu Sun (Journal of Plant Growth Regulation, 2022)

Analyses of Botrytis cinerea-responsive LrWRKY genes from Lilium regale reveal distinct roles of two LrWRKY transcription factors in mediating responses to B. cinerea - Yongyao Fu; Juan Li; Han Wu; Sijia Jiang; Yiyong Zhu; Chunyu Liu; WenJi Xu; Qiang Li; Liping Yang (Plant Cell Reports, 2022)

Electrochemical enhancement of high-efficiency wet removal of mercury from flue gas - Nai-jiao Xu; Sen Li; Yu-hong Fu; Zhao-yang Wang; Li-juan Feng; Ji Wang (Environmental Science and Pollution Research, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A novel BRET based genetic coded biosensor for apoptosis detection at deep tissue level in live animal - Yueling Zhang; Juan Hu; Meijuan Yu; Zhirong Wang; Hucheng Qing; Huheng Fu; Liudi Yuan; Fei Li; Sheng Zhao (Apoptosis, 2021)

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Response of growth characteristics and endogenous hormones of Sophora davidii to low-phosphorus stress - Xin Zhao; Li-Li Zhao; Li-Juan Huang; Xiao-Fu Sun; Pu-Chang Wang (Acta Physiologiae Plantarum, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

Reduction of the Criteria System for Identifying Effective Reservoirs in the Joint Operation of a Flood Control System - Jieyu Li; Ping-an Zhong; Feilin Zhu; Juan Chen; Minzhi Yang; Jisi Fu; Weifeng Liu (Water Resources Management, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Correction to: Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Genome-wide association study reveals the genetic control underlying node of the first fruiting branch and its height in upland cotton (Gossypium hirsutum L.) - Yuanzhi Fu; Chengguang Dong; Juan Wang; Yuanyuan Wang; Chengqi Li (Euphytica, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Genesis of the Angeer Yinwula Pb–Zn deposit, Inner Mongolia, China: constraints from fluid inclusions, C–H–O–S–Pb isotope systematics, and zircon U–Pb geochronology - Han-Lun Liu; Yi Han; Ke-Yong Wang; Wen Li; Jian Li; Wen-Yan Cai; Li-Juan Fu (Arabian Journal of Geosciences, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity - Jing Yang; Yong-Chao Li; Xiu-Ren Zhou; Xin-Juan Xu; Qing-Yun Fu; Chang-Zhong Liu (Natural Product Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Ammonium, nitrate, and urea play different roles for lipid accumulation in the nervonic acid—producing microalgae Mychonastes afer HSO-3-1 - Cheng Yuan; Kai Xu; Juan Sun; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Metabolic, behavioral, and locomotive effects of feeding in five cyprinids with different habitat preferences - Li-Juan Nie; Shi-Jian Fu (Fish Physiology and Biochemistry, 2017)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

The nitrate‐reduction gene cluster components exert lineage‐dependent contributions to optimization of Sinorhizobium symbiosis with soybeans - Li Xue Liu; Qin Qin Li; Yun Zeng Zhang; Yue Hu; Jian Jiao; Hui Juan Guo; Xing Xing Zhang; Biliang Zhang; Wen Xin Chen; Chang Fu Tian (Environmental Microbiology, 2017)
Summary Receiving nodulation and nitrogen fixation genes does not guarantee rhizobia an effective symbiosis with legumes. Here, variations in gene content were determined for three Sinorhizobium species showing contrasting symbiotic efficiency on soybeans. A nitrate‐reduction gene cluster absent in S. sojae was found to be essential for symbiotic adaptations of S. fredii and S . sp. III. In S. fredii , the deletion mutation of the nap (nitrate reductase), instead of nir (nitrite reductase) and nor (nitric oxide reductase), led to defects in nitrogen‐fixation (Fix – ). By contrast, none of these core nitrate‐reduction genes were required for the symbiosis of S . sp. III. However, within the same gene cluster, the deletion of hemN1 (encoding oxygen‐independent coproporphyrinogen III oxidase) in both S. fredii and S . sp. III led to the formation of nitrogen‐fixing (Fix + ) but ineffective (Eff – ) nodules. These Fix + /Eff – nodules were characterized by significantly lower enzyme activity of glutamine synthetase indicating rhizobial modulation of nitrogen‐assimilation by plants. A distant homologue of HemN1 from S. sojae can complement this defect in S. fredii and S . sp. III, but exhibited a more pleotropic role in symbiosis establishment. These findings highlighted the lineage‐dependent optimization of symbiotic functions in different rhizobial species associated with the same host.

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

CXCL10 suppression of hem- and lymph-angiogenesis in inflamed corneas through MMP13 - Nan Gao; Xiaowei Liu; Jiayin Wu; Juan Li; Chen Dong; Xinyi Wu; Xiao Xiao; Fu-Shin X. Yu (Angiogenesis, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Deletion of a target gene in Indica rice via CRISPR/Cas9 - Ying Wang; Lizhao Geng; Menglong Yuan; Juan Wei; Chen Jin; Min Li; Kun Yu; Ya Zhang; Huaibing Jin; Eric Wang; Zhijian Chai; Xiangdong Fu; et al. (Plant Cell Reports, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

One new 19- nor cucurbitane-type triterpenoid from the stems of Momordica charantia - Yong-chao Li; Xin-juan Xu; Jing Yang; Xing-gang Wu; Qing-yun Fu (Natural Product Research, 2016)

Construction and pilot screening of a signature-tagged mutant library of Sinorhizobium fredii - Dan Wang; Yuan Chun Wang; Li Juan Wu; Jian Xin Liu; Pan Zhang; Jian Jiao; Hui Yan; Tao Liu; Chang Fu Tian; Wen Xin Chen (Archives of Microbiology, 2016)

Retraction Note to: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2015)

Behavior, metabolism and swimming physiology in juvenile Spinibarbus sinensis exposed to PFOS under different temperatures - Ji-Gang Xia; Li-Juan Nie; Xia-Mei Mi; Wei-Zhen Wang; Yi-Jie Ma; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Major modes of short-term climate variability in the newly developed NUIST Earth System Model (NESM) - Jian Cao; Bin Wang; Baoqiang Xiang; Juan Li; Tianjie Wu; Xiouhua Fu; Liguang Wu; Jinzhong Min (Advances in Atmospheric Sciences, 2015)
A coupled earth system model (ESM) has been developed at the Nanjing University of Information Science and Technology (NUIST) by using version 5.3 of the European Centre Hamburg Model (ECHAM), version 3.4 of the Nucleus for European Modelling of the Ocean (NEMO), and version 4.1 of the Los Alamos sea ice model (CICE). The model is referred to as NUIST ESM1 (NESM1). Comprehensive and quantitative metrics are used to assess the model’s major modes of climate variability most relevant to subseasonal-to-interannual climate prediction. The model’s assessment is placed in a multi-model framework. The model yields a realistic annual mean and annual cycle of equatorial SST, and a reasonably realistic precipitation climatology, but has difficulty in capturing the spring-fall asymmetry and monsoon precipitation domains. The ENSO mode is reproduced well with respect to its spatial structure, power spectrum, phase locking to the annual cycle, and spatial structures of the central Pacific (CP)-ENSO and eastern Pacific (EP)-ENSO; however, the equatorial SST variability, biennial component of ENSO, and the amplitude of CP-ENSO are overestimated. The model captures realistic intraseasonal variability patterns, the vertical-zonal structures of the first two leading predictable modes of Madden-Julian Oscillation (MJO), and its eastward propagation; but the simulated MJO speed is significantly slower than observed. Compared with the T42 version, the high resolution version (T159) demonstrates improved simulation with respect to the climatology, interannual variance, monsoon-ENSO lead-lag correlation, spatial structures of the leading mode of the Asian-Australian monsoon rainfall variability, and the eastward propagation of the MJO.

Integrated risk assessment method of waterlog disaster in Huaihe River Basin of China - Ju-Liang Jin; Juan Fu; Yi-Ming Wei; Shang-Ming Jiang; Yu-Liang Zhou; Li Liu; You-Zhen Wang; Cheng-Guo Wu (Natural Hazards, 2015)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Ectopic expression of Dendrobium EREB5 gene in Arabidopsis influences leaf morphology - Yuqiang Sun; Ying Shen; Anna Li; Wenfeng Fu; Yu Wang; Qicai Ying; Juan Hao; Brian Jones; Bo Shen; Huizhong Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2014)

Bacterial diversity in saline-alkali ponds rearing common carp (Cyprinus carpio) as revealed by 16S rRNA gene sequences - Jin Qiang Huang; Zhe Liu; Yong Juan Li; Jian Fu Wang (Biologia, 2014)

Polarimetric analysis of multi-temporal RADARSAT-2 SAR images for wheat monitoring and mapping - Juan Xu; Zhen Li; Bangsen Tian; Lei Huang; Quan Chen; Sitao Fu (International Journal of Remote Sensing, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Depression in older patients with advanced colorectal cancer is closely connected with immunosuppressive acidic protein - Rong Li; Jie Yang; Jihua Yang; Weijun Fu; Hua Jiang; Juan Du; Chunyang Zhang; Hao Xi; Jian Hou (Metabolic Brain Disease, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Successful establishment and evaluation of a new animal model for studying the hepatitis B virus YVDD mutant - Yan-Xiu Ma; Zhi-Wei Song; Xu Teng; Li-Juan Fu; Mei-Li Hao; Si-Jia Chen; Wei-Zhen Xu; Hong-Xi Gu (Archives of Virology, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Biosorption of zinc and copper from aqueous solutions by two freshwater green microalgae Chlorella pyrenoidosa and Scenedesmus obliquus - Guang-Jie Zhou; Fu-Qiang Peng; Li-Juan Zhang; Guang-Guo Ying (Environmental Science and Pollution Research, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Risk evaluation of China’s natural disaster systems: an approach based on triangular fuzzy numbers and stochastic simulation - Ju-Liang Jin; Yi-Ming Wei; Le-Le Zou; Li Liu; Juan Fu (Natural Hazards, 2012)

Quantifying the Effects of Conservation Practices on Soil, Water, and Nutrients in the Loess Mesa Ravine Region of the Loess Plateau, China - Xiang-Zhou Xu; Mei-Juan Li; Bin Liu; Shang-Fu Kuang; Shi-Guo Xu (Environmental Management, 2012)

Integrin-mediated signaling contributes to gadolinium-containing-particle-promoted cell survival and G1 to S phase cell cycle transition by enhancing focal adhesion formation - Jin-Xia Li; Li-Juan Fu; Xiao-Gai Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2012)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Two cotton Cys2/His2-type zinc-finger proteins, GhDi19-1 and GhDi19-2, are involved in plant response to salt/drought stress and abscisic acid signaling - Gang Li; Fu-Ju Tai; Yong Zheng; Juan Luo; Si-Ying Gong; Ze-Ting Zhang; Xue-Bao Li (Plant Molecular Biology, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Tunicamycin suppresses cisplatin-induced HepG2 cell apoptosis via enhancing p53 protein nuclear export - Li-Juan Zhang; Zai-Quan Li; Ye-Peng Yang; Xiao-Wen Li; Jia-Fu Ji (Molecular and Cellular Biochemistry, 2009)

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells - Ying Zhang; Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (BioMetals, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Gadolinium-promoted cell cycle progression with enhanced S-phase entry via activation of both ERK and PI3K signaling pathways in NIH 3T3 cells - Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

Characteristics of carbonyl compounds in ambient air of Shanghai, China - Juan Huang; Yanli Feng; Jian Li; Bin Xiong; Jialiang Feng; Sheng Wen; Guoying Sheng; Jiamo Fu; Minghong Wu (Journal of Atmospheric Chemistry, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Isolation of a maize beta-glucosidase gene promoter and characterization of its activity in transgenic tobacco - Riliang Gu; Li Zhao; Ying Zhang; Xiaoping Chen; Juan Bao; Jinfeng Zhao; Zhangying Wang; Junjie Fu; Tingsong Liu; Jianhua Wang; Guoying Wang (Plant Cell Reports, 2006)